Self-organization of nanostructure of lipid-water system - Rashevska, Tamara; Gulyy, Ivan; Ukrainets, Anatoliy; Korenev, I. O. (My University, 2003)
We carried electronic-microscopically researches, which showed stratiform nanostructure of lipids-water system.Ми провели електронно-мікроскопічні дослідження, що показали шаруватість наноструктур системи жир-вода.
Keywords: self-organization; nanostructure; water-lipid system; самоорганізація; наноструктура; водно-ліпідна система; самоорганизация; водно-липидная система; кафедра технології молока і молочних продуктів